Analysis of theoretical concepts of tourism industry management - Niyazbayeva, A.T.; Yessengeldina , A.S. (BUKETOV BUSINESS REVIEW, 2019)
In modern conditions, categorical variables in the tourism industry management, their interrelation between state intervention and self-regulation, as well as the relationship between policy actors and steering modes are developed. Targeted and effective governance is a key requirement for implementing competitive tourism industry. It can facilitate democratic processes, guide and offer the means to make practical progress. The article presents the results of the analysis and systematization of theoretical approaches of foreign authors to the tourism industry management: from the point of view of the government approach, collaboration, public and private partnership, the theory of clusters, political networks and stakeholders theory. It is revealed that there are conceptual problems associated with the analysis of the theoretical foundations of management and tourism policy in general. The role of the central government in the development of a coherent and effective policy in the field of tourism is defined. Four modes of coordination in the tourism industry management are identified: hierarchies, markets, networks and communities.